Parental Awareness of Gender Stereotypes in Early Childhood Development - Aryal, Shobha (Journal of Multidisciplinary Research Advancements, 2024)
The study aimed to address the gaps in understanding the significant impact of parental supervision and discourse on children's interpretation of gender norms in society. To achieve this, a comprehensive methodology was employed, involving an in-depth analysis of parental views, language use, toy and clothing choices, and activities. The findings of the study highlighted the crucial role of parental influence in either reinforcing or challenging established gender norms, thus impacting children's choices and self-expression. This research sheds light on the importance of parental involvement in cultivating a more inclusive and diverse understanding of gender for the next generation. Furthermore, the article delved into the complex ways in which parents shape their children's conceptions of gender in the early years of their lives. The study underscored the significance of parental supervision and emphasized how parental attitudes are transmitted to children, influencing their perspectives and actions with respect to gender stereotypes. Additionally, the research explored several facets of parental discourse, clarifying the ways in which language and conversations within the home have significant effects on children's understanding of societal gender norms.